2021
DOI: 10.1002/cam4.4271
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, determinants, and outcomes of SARS‐COV‐2 infection among cancer patients. A population‐based study in northern Italy

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 23 publications
(54 reference statements)
1
14
3
1
Order By: Relevance
“…Italian data published so far were mostly collected during the first wave showing seroprevalence below 5% among the general population resident in several Italian regions, with data below 1% in most Southern regions and up to 7.5% in Lombardia [ 15 , 16 ]. A study carried out in a North Eastern Italian region including also the last quarter of 2020 (the middle of the second wave in Italy) documented a prevalence up to 16% [17] . In the latter study, a risk reduction of 41% was found in cancer patients, who like patients with CF, are considered a high-risk population.…”
Section: Discussionmentioning
confidence: 99%
“…Italian data published so far were mostly collected during the first wave showing seroprevalence below 5% among the general population resident in several Italian regions, with data below 1% in most Southern regions and up to 7.5% in Lombardia [ 15 , 16 ]. A study carried out in a North Eastern Italian region including also the last quarter of 2020 (the middle of the second wave in Italy) documented a prevalence up to 16% [17] . In the latter study, a risk reduction of 41% was found in cancer patients, who like patients with CF, are considered a high-risk population.…”
Section: Discussionmentioning
confidence: 99%
“…After a preliminary review and the elimination of duplicates, 5328 papers were screened and chosen for further evaluation. A total of 58 studies (Adejumo et al 2021 ; Akhtar et al 2021 ; Alpert et al 2021 ; Arslan et al 2021 ; Azarkar et al 2021 ; Baker et al 2021 ; Benelli et al 2020 ; Bennett et al 2021 ; Bergman et al 2021 ; Bernard et al 2021 ; Bhargava et al 2021 ; Borobia et al 2020 ; Pinto et al 2020 ; Chai et al 2021 ; Fu et al 2021 ; Chudasama et al 2021 ; Costa et al 2021 ; Duanmu et al 2020 ; Gold et al 2020 ; Görgülü et al 2020 ; Goyal et al 2020 ; Gude-Sampedro et al 2021 ; Guo et al 2021 ; Joharatnam-Hogan et al 2020 ; Katkat et al 2021 ; Kim et al 2021 ; Kokturk et al 2021 ; Liang et al 2021 ; Sun et al 2021 ; Cavanna et al 2020 ; Lunski et al 2021 ; Martinot et al 2021 ; Mirgh et al 2021 ; Miyashita et al 2020 ; Nakamura et al 2021 ; Nikpouraghdam et al 2020 ; Panda et al 2022 ; Péron et al 2021 ; Poli et al 2022 ; Li et al 2020a , b ; Reddy et al 2021 ; Regina et al 2020 ; Ricoca-Peixoto et al 2020 ; Giorgi-Rossi et al 2020 ; Rugge et al 2020 ; Erdal et al 2021 ; Sami et al 2020 ; Santorelli et al 2021 ; Pérez-Segura et al 2021 ; Serraino et al 2021 ; Shahidsales et al 2021 ; Sorouri et al 2020 ; Stroppa et al 2020 ; Tehrani et al 2021 ; Vergara et al 2021 ; Vila-Corcoles et al 20...…”
Section: Resultsunclassified
“…A total of 42 studies (Akhtar et al 2021 ; Alpert et al 2021 ; Arslan et al 2021 ; Azarkar et al 2021 ; Baker et al 2021 ; Benelli et al 2020 ; Bennett et al 2021 ; Bernard et al 2021 ; Bhargava et al 2021 ; Borobia et al 2020 ; Pinto et al 2020 ; Chai et al 2021 ; Fu et al 2021 ; Gude-Sampedro et al 2021 ; Guo et al 2021 ; Joharatnam-Hogan et al 2020 ; Katkat et al 2021 ; Kim et al 2021 ; Kokturk et al 2021 ; Liang et al 2021 ; Sun et al 2021 ; Lunski et al 2021 ; Martinot et al 2021 ; Mirgh et al 2021 ; Miyashita et al 2020 ; Péron et al 2021 ; Poli et al 2022 ; Li et al 2020a , b ; Reddy et al 2021 ; Ricoca Peixoto et al 2020 ; Giorgi-Rossi et al 2020; Rugge et al 2020 ; Erdal et al 2021 ; Pérez-Segura et al 2021 ; Serraino et al 2021 ; Shahidsales et al 2021 ; Sorouri et al 2020 ; Stroppa et al 2020 ; Vergara et al 2021 ; Vila-Corcoles et al 2021 ; Zhang et al 2021 ; Zhou et al 2021 ) were included in the analysis to compare the mortality rates of cancer and non-cancer patients infected with SARS-CoV-2. There were a total of 557,053 participants, of whom 21,599 were cancer patients.…”
Section: Resultsmentioning
confidence: 99%
“…2 Individuals of any age with underlying medical conditions, older adults (≥65 years), pregnant women, and smokers are at higher risk of severe illness. 3 , 4 , 5 , 6 Those in the healthcare sector are disproportionately affected by COVID‐19. 7 , 8 Despite sustained epidemics in many countries, a systematic review of studies including 6.3 million individuals from 60 countries indicated that by mid‐2021 the majority of the world's human population was still susceptible to SARS‐CoV‐2 infection, with a pooled seroprevalence of approximately 10%.…”
Section: Introductionmentioning
confidence: 99%
“…As of January 2022, 388 million people worldwide have been cumulatively reported to be infected with SARS‐CoV‐2 and 5.7 million deaths registered 2 . Individuals of any age with underlying medical conditions, older adults (≥65 years), pregnant women, and smokers are at higher risk of severe illness 3–6 . Those in the healthcare sector are disproportionately affected by COVID‐19 7,8 .…”
Section: Introductionmentioning
confidence: 99%